DIALOG INTERAKTIF PENGENALAN ANAK BERKEBUTUHAN KHUSUS PADA GURU RA DI KOTA PEKANBARU - Ida Windi Wahyuni; Raihana Raihana; Alucyana Alucyana; Dian Tri Utami (Kreasi: Jurnal Pengabdian Masyarakat, 2021)
Children with special needs are defined as children have physical, mental, intellectual, and emotional differences with other children so that special learning is needed. Early childhood education institutions and kindergarten teachers should know and understand the handling of children with special needs. This activity was carried out with the aim that RA teachers in the city of Pekanbaru know and understand to handle Children with Special Needs (ABK) in the school environment. The implementation of this activity uses the community method, namely 76 RA teachers divided into 5 groups and carried out in 5 RA. The form of this activity is counseling and interactive dialogue. The result of this activity is that teachers gain additional knowledge and understanding from before about Children with Special Needs and to handle them at school.